Shear Bond Strength of Orthodontic Brackets to Composite Restorations Using Universal Adhesive - Soodeh Tahmasbi; Mohammadreza Badiee; Maryam Modarresi (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: The dental adhesives may have the potential to increase the bond strength of orthodontic brackets to composite resin and it would be highly desirable if adequate bracket-composite bond strength could be yielded by using these adhesives without the need for surface roughening. Purpose: The purpose of this study was to measure the shear bond strength (SBS) of metal brackets to composite restorations by use of a universal adhesive compared with a conventional adhesive. Materials and Method: In this in vitro, experimental study, 45 composite discs measuring 6 mm in diameter and 4 mm in thickness were fabricated and assigned to three groups (n=15). In the group 1, discs were etched with 37% phosphoric acid for 15 seconds and Scotchbond Universal was then applied. Discs were roughened by diamond bur in the group 2 and were subjected to the application of Scotchbond Universal. In the group 3, conventional adhesive (Single Bond 2) was applied after roughening the discs by diamond bur. Metal brackets were then bonded to discs and after thermocycling, the SBS was measured by an Instron machine. The mode of failure and adhesive remnant index (ARI) score were determined using stereomicroscope. Data were analyzed by SPSS version 18, one-way ANOVA, and the Kruskal Wallis test. Results: The surface roughening plus universal adhesive group showed the highest SBS (11.90 MPa) but according to one-way ANOVA, the difference in this regard among the three groups was not statistically significant (p= 0.94). Most samples showed ARI score of 4. Conclusion: Universal adhesive can provide sufficient bond strength as high as that provided by conventional adhesives for orthodontic bracket bonding to composite restorations even in absence of surface roughening by bur.